DNA REPLICATION PATTERNS AND CHROMOSOMAL PROTEIN SYNTHESIS IN OPOSSUM LYMPHOCYTES IN VITRO - Schneider, Lawrence K. (The Rockefeller University Press, 1967)
DNA replication patterns were determined in the autosomes and sex chromosomes of phytohemagglutinin-stimulated lymphocytes from the opossum (Didelphis virginiana) by employing thymidine-(3)H labeling and high-resolution radioautography. Opossum chromosomes are desirable experimental material due to their large size, low number (2n = 22), and morphologically distinct sex chromosomes. The autosomes in both sexes began DNA synthesis synchronously and terminated replication asynchronously. One female X chromosome synthesized DNA throughout most of the S phase. Its homologue, however, began replication approximately 3.5 hr later. The two X's terminated DNA synthesis synchronously, slightly later than the autosomes. This form of late replication, in which one X chromosome begins DNA synthesis later than its homologue but completes replication at the same time as its homologue, is apparently unique in the opossum. The male X synthesized DNA throughout S while the Y chromosome exhibited late-replicating characteristics. The two sex chromosomes completed synthesis synchronously, slightly later than the autosomes. Grain counts were performed on all chromosomes to analyze trends in labeling intensity at hourly intervals of S. By analyzing the percent of labeled mitotic figures on radioautographs at various intervals after introduction of arginine-(3)H, chromosomal protein synthesis was found not to be restricted to any portion of interphase but to increase throughout S and into G(2).